Association of TLR2 haplotypes encoding Q650 with reduced susceptibility to ovine Johne’s disease in Turkish sheep - Yaman, Yalçın (Sci Rep, 2021)
Ovine Johne’s disease (OJD) is caused by Mycobacterium avium subsp. paratuberculosis (MAP) and carries a potential zoonotic risk for humans. Selective breeding strategies for reduced OJD susceptibility would be welcome tools in disease eradication efforts, if available. The Toll-like receptor 2 gene (TLR2) plays an important signaling role in immune response to MAP, and missense variants are associated with mycobacterial infections in mammals. Our aim was to identify and evaluate ovine TLR2 missense variants for association with OJD in Turkish sheep. Eleven TLR2 missense variants and 17 haplotype configurations were identified in genomic sequences of 221 sheep from 61 globally-distributed breeds. The five most frequent haplotypes were tested for OJD association in 102 matched pairs of infected and uninfected ewes identified in 2257 Turkish sheep. Ewes with one or two copies of TLR2 haplotypes encoding glutamine (Q) at position 650 (Q650) in the Tir domain were 6.6-fold more likely to be uninfected compared to ewes with arginine (R650) at that position (CI(95) = 2.6 to 16.9, p-value = 3.7 × 10(–6)). The protective TLR2 Q650 allele was present in at least 25% of breeds tested and thus may facilitate selective breeding for sheep with reduced susceptibility to OJD.